TEACHING AT KINDERGARTEN: NOTES FROM THE ASSUMPTIONS OF CULTURAL-HISTORICAL PSYCHOLOGY - Barbosa, Eliza Maria [UNESP]; Silva, Janaina Cassiano; Silva, Altina Abadia da (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
In this essay we discuss some theoretical-practical assumptions about the organization of teaching children from two to three years in daycare, indicating their contributions to enrichment of manipulative object activity characteristic of the development of children at that age. In order to reach this goal, we reflect on the permanence in the current scenario of children's education of characteristic features of functions assumed by educational institutions in other historical moments and we discuss the constituent elements of the formation of the articulated consciousness to the concepts of language and manipulatory activity. We reaffirm from the principles of historical-dialectical materialism that children in early childhood begin the journey of producing their existence through historically conditioned relations, under the principle of cooperation between men and this relationship of dependence provides them with the consciousness that they live in society. Through the constructs of Cultural-Historical Psychology we demonstrate the decisive influence that adults/educators have on the genesis of the voluntary act in children and how their language, and then that of children themselves, plays a regulating role of the other psychological functions, among them attention, perception and memory. We urge education at all levels to recognize that its function of fully integrating the singular human being occurs under historically and socially determined conditions. This allows us to conclude that educational practices consciously committed to the humanization of children is the possible way to overcome mechanisms that historically annihilate their possibilities of human-generic development.
Keywords: Early Childhood; Kindergarten; Teaching; Cultural-Historical Psychology